Dr: Perbandingan Antara Moderasi Dan Wasathiyah Dalam Tinjauan Pendidikan Islam - Ali Muddin Jailani; Bambang Supradi (Institut Agama Islam Sumatera Barat Pariaman, 2026)
Some scholars tend to equate the concept of moderation with wasathiyah, although the two differ in terms of definition, conceptual background, and implementation. This study employs a literature review approach using content analysis, applied flexibly through conceptual construction analysis. The findings indicate that moderation and wasathiyah share several commonalities, yet also reveal fundamental differences in terms of their definitions, epistemological foundations, and underlying values. The concept of religious moderation has developed within the context of modern thought that emphasizes universal values as its primary foundation, whereas the concept of wasathiyah is rooted in Islamic teachings derived from revelation and possesses a universal orientation in its application. In the context of Islamic education, the concept of wasathiyah education is viewed as having closer relevance to the framework of Islamic educational values compared to the term religious moderation. Wasathiyah education implies the formation of students’ understanding, attitudes, and behavior grounded in revelatory values.